ChemInform Abstract: Towards Uniform Iodine Catalysis: Intramolecular C—H Amination of Arenes under Visible Light. Issue 48 (10th November 2016) - Martinez, Claudio; Bosnidou, Alexandra E.; Allmendinger, Simon; Muniz, Kilian
Abstract: A mild protocol is developed for the intramolecular aryl amination reaction using visible light and iodine as catalysts in the presence of a mild hypervalent iodine oxidant.